2016
DOI: 10.1371/journal.pone.0153141
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the 10-Valent Pneumococcal Conjugate Vaccine (PCV-10) in Children in Chile: A Nested Case-Control Study Using Nationwide Pneumonia Morbidity and Mortality Surveillance Data

Abstract: BackgroundThe ten-valent pneumococcal conjugate vaccine (PCV10) was introduced into the Chilean National Immunization Program (NIP) in January 2011 with a 3+1 schedule (2, 4, 6 and 12 months) without catch-up vaccination. We evaluated the effectiveness of PCV10 on pneumonia morbidity and mortality among infants during the first two years after vaccine introduction.MethodsThis is a population-based nested case-control study using four merged nationwide case-based electronic health data registries: live birth, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 24 publications
1
28
1
6
Order By: Relevance
“…We get some approximation from randomized controlled trials and case-control analyses, both of which provide an estimate of the direct protection obtained by receiving the vaccine, although these do not capture the indirect effect of the vaccine that results from disrupting transmission. The estimates of the PCV-related reduction in hospitalizations of infants for all-cause pneumonia produced by the synthetic controls approach are larger than the both 10% against clinical pneumonia found by a randomized controlled trial in Latin America (12) and the 11% reduction in pneumonia hospitalizations in children less than 2 y of age found by a case-control study in Chile (23). Given that trend analyses capture both direct and indirect effects of the vaccine, it is reasonable that our estimates would be larger than those found by clinical trials or case-control studies, which only capture direct effects.…”
contrasting
confidence: 56%
“…We get some approximation from randomized controlled trials and case-control analyses, both of which provide an estimate of the direct protection obtained by receiving the vaccine, although these do not capture the indirect effect of the vaccine that results from disrupting transmission. The estimates of the PCV-related reduction in hospitalizations of infants for all-cause pneumonia produced by the synthetic controls approach are larger than the both 10% against clinical pneumonia found by a randomized controlled trial in Latin America (12) and the 11% reduction in pneumonia hospitalizations in children less than 2 y of age found by a case-control study in Chile (23). Given that trend analyses capture both direct and indirect effects of the vaccine, it is reasonable that our estimates would be larger than those found by clinical trials or case-control studies, which only capture direct effects.…”
contrasting
confidence: 56%
“…Before-after was the most common study design, and surveillance the most common data source used in the reported studies (Table 1). A total of 6 studies analyzed mortality: 2 evaluated PCV impact on pneumococcal meningitis deaths [19, 20], 2 evaluated impact on all-cause deaths [21, 22], and 3 analyzed deaths due to pneumonia [2224]. …”
Section: Resultsmentioning
confidence: 99%
“…Esta reducción alcanza a 61,9% en niños bajo 2 años de edad 6 . Por otra parte, en un estudio caso control en niños vacunados con PCV10 se pudo estimar una efectividad de la vacuna de 20,7% para prevenir eventos de neumonía y de 71,5% para muertes por neumonía 7 . Luego de la introducción de la vacuna, en personas mayores de 60 años el número de casos anuales de ENI notificados al ISP no se ha modificado.…”
Section: Impacto En Chileunclassified